Stunting Eradication Policy in Palembang City: Analysis of Government Involvement in Improving Child Welfare - Doris Febriyanti; Nina Yuslaini (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the factors influencing the success of stunting reduction policies in Palembang City, focusing on internal and external elements that shape policy outcomes. The research utilizes a descriptive case study approach, analyzing data through interviews, observations, and document reviews. Key internal factors include government leadership, inter-agency coordination, human resources, and the utilization of data and technology. External factors encompass social and cultural aspects, economic conditions, support from private sectors, and national policies. The findings highlight the significance of strong leadership and effective collaboration among stakeholders, emphasizing the role of community involvement and technological advancements in addressing stunting. The study concludes with recommendations to enhance policy implementation and sustain long-term success in reducing stunting prevalence.